Harnessing Large Model Technology for Higher Education Reform: Opportunities, Challenges, and Strategic Solutions - Jing Lei; Song, Jia-Qing; Shan Jiang; Jing Li; Yan Liang (Ilmu Inovasi Nusantara, 2025)
The rapid development of information technology has brought significant transformations, including adopting large model technology as an innovative tool for data analysis and processing. This technology is increasingly permeating the field of higher education, offering substantial opportunities for educational innovation and reform. This study explores large model technology's current application, advantages, and impacts on higher education reform. The methodology involves analyzing case studies of its application in teaching, scientific research, and educational management. The findings indicate that large model technology provides considerable benefits, such as improving teaching effectiveness, fostering research innovation, and optimizing educational resource allocation. However, its implementation also faces significant challenges, including high technical barriers, data security and privacy protection risks, and threats to educational equity. In response to these challenges, the study proposes several recommendations, including strengthening technological infrastructure, enhancing the digital skills of educators and students, and developing more robust data management systems. These findings aim to serve as a valuable reference for the innovation and development of higher education in the modern technological era. Consequently, the strategic integration of large model technology is essential to addressing these challenges and supporting the sustainable advancement of educational goals